ANALISIS PERILAKU BERKENDARA PADA TITIK U-TURN DI KOTA PALANGKA RAYA (STUDI KASUS JALAN TJILIK RIWUT – JALAN YOS SUDARSO – JALAN AKHMAD YANI) - Jaridieni, Ira; Desriantomy, Desriantomy; Riani, Desi (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Tjilik Riwut, Yos Sudarso and Akhmad Yani streets are main road in Palangka Raya city. On that streets there are many shopping malls, shops, offices and schools. Because of that many activities on the side of the road around the u-turn point, making the roads are often congested lane in the direction of flow and the lane in the opposite direction, so that when the rider wants to do a rotating direction, the vehicle needs to do  a normal approach as reduce speed or stop. This study aims to determine the driving behavior when turning direction and the driving behavior that could potentially cause traffic accidents at u-turn point,then to know the potential of accidents and to investigate the mathematical model between the average time of vehicle doing the twist direction with traffic volume on the streets. Based on analysis, there are seven dominant driving behavior while doing the twist direction, three of them are potentially cause accident i.e. do the twist direction against flow of traffic, rotate toward at the point that is prohibited as well as cross vehicle the same rotating direction without regard to other vehicle was speeding. The biggest accident potential is 18.070% by motor cycles at Tjilik Riwut street while the best mathematical model is exponential equation at Akhmad Yani street.